2017
DOI: 10.1039/c7ob00059f
|View full text |Cite
|
Sign up to set email alerts
|

Access to π-conjugated azaindole derivatives via rhodium(iii)-catalyzed cascade reaction of azaindoles and diazo compounds

Abstract: Diazo compounds play an important role as a coupling partner in the synthesis of unique π-conjugated 7-azaindole derivatives via rhodium(iii)-catalyzed double C-H activation/cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The group-directed ortho -alkylation with diazocompounds or via addition to alkenyl esters, followed by intramolecular activation of the azaindole C2, and finally by dehydration or β-H elimination, results in the products in Scheme 157H and I . 972 , 973 The reaction with alkynes, occurring as previously reported for other DGs, was also investigated ( Scheme 157J and K ). 974 , 975 Interesting in this respect is the reaction with 3 equiv.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 99%
“…The group-directed ortho -alkylation with diazocompounds or via addition to alkenyl esters, followed by intramolecular activation of the azaindole C2, and finally by dehydration or β-H elimination, results in the products in Scheme 157H and I . 972 , 973 The reaction with alkynes, occurring as previously reported for other DGs, was also investigated ( Scheme 157J and K ). 974 , 975 Interesting in this respect is the reaction with 3 equiv.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 99%
“…Next, Rh(III)‐catalyzed carbenoid insertion/coupling cascade was reported by Dong and co‐workers which leads to the formation of π‐conjugated azaindoles derivatives ( 126 and 127 ) via double C−H bond activation (Scheme 34). [45] To optimize the reaction conditions they screened a series of additives like AgOAc, AcOH, Cu(OAc) 2 , NaOAc, PivOH, TFA, 1‐AdCOOH and 3‐hydroxy pivalic acid while using 5 mol% of [Cp*RhCl 2 ] 2 as a catalyst and observed best yield with 1 equivalent of 3‐hydroxy pivalic acid. Next, a series of N‐aryl 7‐azaindoles ( 91 ) was examined and it was observed that both electron‐donating as well as electron‐withdrawing substituents were well tolerated and provide moderate to good yield of the corresponding products.…”
Section: Rh(iii)‐catalyzed Reactionsmentioning
confidence: 99%
“…Among them, aza‐indole derivatives have received great attention due to their diverse biological and chemical properties . Recently, Dong and co‐workers reported a rhodium(III)‐catalyzed cascade reaction from 7‐azaindoles 85 and diazo compounds to access π‐conjugated azaindole derivatives 86 (Scheme ) . Two isomers are formed in most cases.…”
Section: Synthesis Of Aza‐fused Scaffoldsmentioning
confidence: 99%